IDENTIFIKASI HASIL TANGKAPAN IKAN DENGAN MENGGUNAKAN ALAT TANGKAP PUKAT PANTAI DI PERAIRAN PANTAI LAMPU SATU KABUPATEN MERAUKE - Maria Welliken; Abdullah Sarijan (AGRICOLA, 2012)
Lampu Satu area is potential coastal waters tend to decline. This is because the use of fishing gear that does not fit the rules. Most of the fishing fleets in coastal waters Lampu Satu  is the outboard. This type of fishing gear used by fishermen in coastal waters including the form of lamp one beach seine fishing gear, gill nets fixed, and tramell net. The reduced potential for coastal waters in the form of Lampu Satu fish, prompting the need for efforts to preserve threatened with extinction, so it needs to do research on the identification of fish as a rare start in efforts to preserve fish. The method used in this study is observation; interviews; descriptions, and literature study. Sampling was conducted at three stations of station I (Lampu Satu Tower), station II (Bina Loka) and station III (Imbuti) with details of the three sampling times during the two weeks in June to July 2011. Data analyze using descriptive methods.  The results Lampu Satu coastal waters have 18 species of fish caught by beach seine, a classification which found four classes, 10 orders, and 17 familiidi earn 18 species of fish that includes Macrones nemurus; Pseudocienna amovensis; Pomadasys argenteus; Aspericovina jubata; Eleutheronema tetradactylum; Mugil cephalus; Kurtus gulliveri; Sardinella fimbriat; Plotosus canius; Periophthalmodon schlosseri; Diodon holocanthus; Dermogenys pusilla; Cynoglossus lingua; Trygon sephen; Gerres filamentosus; Lates calcarifer; Trychiurus savala; and Rhinoptera javanica. The results of measurements of parameters of chemical physics coastal waters Lampu Satu is at the station I (Lampu  Satu Tower) with a temperature of 290celcius; water pH 7.8; salinity of  24 ppt. Station II (Bina Loka) with a temperature of 300celcius; water pH 8.3; salinity of 26 ppt. Station III (Imbuti) with a temperature of 290celcius; water pH 8.1; salinity of 29 ppt.